Pengaruh Volume Perdagangan Saham dan Ukuran Perusahaan terhadap Return Saham Perusahaan yang Terdaftar pada Indeks LQ45 - Sustrianah Sustrianah (JEM Jurnal Ekonomi dan Manajemen, 2020)
This study aims to determine the effect of Trading Volume Activity and Company Size on Stock Returns in companies listed on the LQ45 Index. This research uses quantitative methods. The population in this study were companies listed on the LQ45 Index for the period 2015 - 2019. The sample selection used a purposive sampling method. There are 9 companies that meet the criteria as research samples, so the research data is 45 data. The data collection techniques used were document review, data analysis in the form of annual financial reports, previous research journals and other literature related to research problems. The data analysis technique used is multiple linear regression analysis. Data analysis using IBM SPSS statistics, 24.0 software. The results showed that partially the Trading Volume Activity variable had no significant effect on Stock Returns. Firm Size Variable has a positive and significant effect on Stock Return. The coefficient of determination shows that the value of Adjusted R Square is 0.168. This means that the ability of the independent variable in explaining the variation of the dependent variable is 16.8% while 83.2% is explained by other independent variables that are not explained in this study.